The Law of Maninggian Janjang against Perpetrators of Adultery from Saddu al-dzari’ah's Perspective - Sudarman, Revoranda; Azwar, Zainal (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
The practice of "maninggian janjang" against members of the adulterous community in the Baso District, Agam Regency, West Sumatra has its own peculiarities. This maninggian janjang punishment only applies there and the most interesting thing is that they punish a community if a member of the community commits adultery.  The concept of punishment like this is not applied in Islamic law, even though Baso sub-district people are Minangkabau people who have a philosophy of life "adat basandi syarak, syarak basandi kitabullah". This research will examine how the saddu al-dzari'at ijtihad method looks at the collective imposition of punishment on adultery offenders. This ijtihad method is used not only because it has similar principles with the punishment of maninggian janjang but also for the consideration of Imam Syafi'I who did not totally reject the concept of saddu al-dzari'ah. This type of research is empirical research using a qualitative approach. Data is obtained by conducting face-to-face interviews which are analyzed through coding techniques. The validity and reliability of the data were tested through peer debriefing techniques followed by review by the reviewer. This study found that maninggian janjang is in accordance with the saddu al-dzari'at method in which the way of ignoring adultery in a community is closed by threatening punishment collectively if there are members of the community who commit adultery. Meanwhile, the abolition of punishment through fines should be adjusted to the economy of the punished people so that the purpose of this maninggian janjang punishment is achieved, namely to provide fear and deterrent effect.